Proposed clinical definition for oral submucous fibrosis - More, Chandramani B. (J Oral Biol Craniofac Res, 2019)
Oral Submucous Fibrosis (OSMF) is an insidious, chronic, complex, crippling, debilitating, irreversible, progressive, scarring, potentially malignant and collagen metabolic disorder, induced by a known carcinogen areca nut; wherein the oral mucosa, and occasionally the pharynx and esophagus is subjected to various pathological changes with significant clinical manifestations at different stages of progression, leading to functional morbidity; and with a risk of malignant transformation in the overlying epithelium. Although the condition is mainly diagnosed based on classic clinical manifestations, the commonly used existing definition for oral submucous fibrosis is primarily based on histological features. The authors have conducted extensive clinical research studies on OSMF and intends to propose a new clinical definition as ‘a debilitating, progressive, irreversible collagen metabolic disorder induced by chronic chewing of areca nut and its commercial preparations; affecting the oral mucosa and occasionally the pharynx and esophagus; leading to mucosal stiffness and functional morbidity; and has a potential risk of malignant transformation.’ Thus, a new clinical definition is put forward so as to assist the academicians, researchers and clinicians in terming and grouping this disease according to its clinical and biological behaviour for its subsequent management.